2004
DOI: 10.1242/jeb.01016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gene expression associated with acclimation to constant temperatures and fluctuating daily temperatures in an annual killifishAustrofundulus limnaeus

Abstract: The effect of temperature is manifested at every level of biological organization, from complex behaviors to molecular motion. Changes in temperature affect the fluidity of lipid membranes, the conformational mobilities and activities of proteins, and the stability of DNA duplexes (Hochachka and Somero, 2002). Because these thermal effects have such major consequences for cellular function, organisms typically manifest extensive evolutionary adaptations that establish distinct thermal optima and limits for phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
326
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(351 citation statements)
references
References 57 publications
21
326
1
3
Order By: Relevance
“…Gracey et al 2008); however, the constitutive HSC70 has been designated the main heat-dependant HSP70 family member in the Pacific white shrimp (Litopenaeus vannamei; Wu et al 2008). This latter example may be species specific as there is increasing evidence that although HSC70 may upregulated by acute heat stress, it is often more likely to correlate with longer-term chronic stress such as that described here, in fluctuating temperature regimes (Podrabsky and Somero 2004;Todgham et al 2006) and under environmentally diverse bio-geographical distributions (Fangue et al 2006;Place et al 2008). The great flexibility of the HSP70 gene complex means that if it is to be used as an environmental biomarker, clearly as many family members as possible should be surveyed under a number of different conditions over both acute and chronic timescales.…”
Section: Hsp70 Gene Family Expressionmentioning
confidence: 78%
“…Gracey et al 2008); however, the constitutive HSC70 has been designated the main heat-dependant HSP70 family member in the Pacific white shrimp (Litopenaeus vannamei; Wu et al 2008). This latter example may be species specific as there is increasing evidence that although HSC70 may upregulated by acute heat stress, it is often more likely to correlate with longer-term chronic stress such as that described here, in fluctuating temperature regimes (Podrabsky and Somero 2004;Todgham et al 2006) and under environmentally diverse bio-geographical distributions (Fangue et al 2006;Place et al 2008). The great flexibility of the HSP70 gene complex means that if it is to be used as an environmental biomarker, clearly as many family members as possible should be surveyed under a number of different conditions over both acute and chronic timescales.…”
Section: Hsp70 Gene Family Expressionmentioning
confidence: 78%
“…We also detected the strong induction of a number of high-mobility group proteins (HMG1, HMGT1, HMG4, and NHPX) that modulate transcription through the alteration of chromosome conformation, suggesting that chromosomal DNA secondary structure might also be disturbed in the cold. In killifish, the expression of another high-mobility group protein, HMGB1, has also been shown to fluctuate with cycling temperature, providing further evidence that this gene family is involved in temperature responses (18). The identification of genes involved in both RNA processing and chromosomal architecture suggests an important function of cold acclimation is to regulate nucleic acid structures.…”
Section: Resultsmentioning
confidence: 98%
“…This phenomenon, known as heat hardening (Bowler, 2005), is a very important inducible stress tolerance mechanism in many organisms, both terrestrial and aquatic, inhabiting variable environments (Maness and Hutchinson, 1980;Rutledge et al, 1987;Middlebrook et al, 2008;Bilyk et al, 2012). Previous studies have shown fluctuating thermal environments increase thermal tolerance (Feldmeth et al, 1974;Otto, 1974;Threader and Houston, 1983;Woiwode and Adelman, 1992;Schaefer and Ryan, 2006;Oliver and Palumbi, 2011;Manenti et al, 2014;Kern et al, 2015), with intertidal species exposed to tidal cycle fluctuations being more stress-tolerant than those that are exposed to constant temperatures (Tomanek and Sanford, 2003;Podrabsky and Somero, 2004;Todgham et al, 2006;Giomi et al, 2016). Taken together, these studies suggest that the thermal physiology of intertidal organisms is likely modulated by the natural variability inherent with the ebb and flow of tides.…”
Section: Introductionmentioning
confidence: 99%